2019
DOI: 10.20960/nh.2435
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of body composition in cancer patients using CT planning scan at the third lumbar vertebra

Abstract: La carne es un alimento muy bien aceptado por sus propiedades organolépticas. Es fundamental en el desarrollo del ser humano por su alto valor nutritivo. Fuente importante de minerales, vitaminas y proteínas de elevada calidad. Su importancia nutricional está en consonancia con su repercusión económica. En este artículo, y a la luz del comunicado recientemente emitido por la OMS sobre el peligro para la salud, particularmente de cáncer, del consumo elevado de carne roja y/o procesada y dada la alarma social oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
0
17
0
2
Order By: Relevance
“…Abdominal and pelvic CT images of all recruited patients before the surgery were analysed retrospectively. Numerous studies have confirmed that the area of skeletal muscle and adipose tissue in CT cross-sectional images of the L3 vertebral level scan performed in the supine position is closely related to the total body muscle and fat mass (25,26). Therefore, skeletal muscle area at the level of lumber vertebral L3 was measured in GIST patients.…”
Section: Measurement Of Muscle Mass and Strengthmentioning
confidence: 95%
“…Abdominal and pelvic CT images of all recruited patients before the surgery were analysed retrospectively. Numerous studies have confirmed that the area of skeletal muscle and adipose tissue in CT cross-sectional images of the L3 vertebral level scan performed in the supine position is closely related to the total body muscle and fat mass (25,26). Therefore, skeletal muscle area at the level of lumber vertebral L3 was measured in GIST patients.…”
Section: Measurement Of Muscle Mass and Strengthmentioning
confidence: 95%
“…Both the visceral adipose tissue (VAT) and the subcutaneous adipose tissue (SAT) were segmented at the center plane of the 3 rd lumbar vertebra on axial CT-scans (Fig 1). This CT plane was chosen to gain the highest comparability with existing studies [14,15]. Participants with missing data were omitted from the analysis.…”
Section: Assessment Of Adipose Tissue Compositionmentioning
confidence: 99%
“…Sarcopenia and body composition can be evaluated by radiological imaging techniques at the level of the third lumbar vertebra, such as computed tomography (CT) and magnetic resonance imaging (MRI) [ 17 , 18 , 19 , 20 ]. These high-resolution imaging systems are reliable and easy tools to quantify muscle mass and detect sarcopenia in its early stages.…”
Section: Introductionmentioning
confidence: 99%